High-accuracy mass spectrometry for fundamental studies - Kluge, Heinz-Jürgen (European journal of mass spectrometry, 2010)
Mass spectrometry for fundamental studies in metrology and atomic, nuclear and particle physics requires extreme sensitivity and efficiency as well as ultimate resolving power and accuracy. An overview will be given on the global status of high-accuracy mass spectrometry for fundamental physics and metrology. Three quite different examples of modern mass spectrometric experiments in physics are presented: (i) the retardation spectrometer KATRIN at the Forschungszentrum Karlsruhe, employing electrostatic filtering in combination with magnetic?adiabatic collimation?the biggest mass spectrometer for determining the smallest mass, i.e. the mass of the electron anti-neutrino, (ii) the Experimental Cooler-Storage Ring at GSI?a mass spectrometer of medium size, relative to other accelerators, for determining medium?heavy masses and (iii) the Penning trap facility, SHIPTRAP, at GSI?the smallest mass spectrometer for determining the heaviest masses, those of super-heavy elements. Finally, a short view into the future will address the GSI project HITRAP at GSI for fundamental studies with highly-charged ions.
Gesehen am 15.03.2023